(3JGL GdJaGSjQ dcdGe Gdedc GdcHjQs - (3GdejQZfj , eMeO YKeGf Hf eMeO CHj HcQ Hf YHO Gddg GdejQZfj GdeMLhH,J (B1268 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi GdcHQjGA QOGAg hGdYXeI GRGQg aef fGRYg s
(3BNQgG (B:s
(3Je GdbSe GdChd ef cJGH JGL GdJaGSjQ s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B262 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B286s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B209s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs